Pembentukan Pandemic Treaty dalam Menjawab Urgensi Keadilan Tata Kelola Kesehatan Global Pasca COVID-19 - Nur Pratama, Rama Agung; Hafriady, Muhammad; Rasendriya, Rasendriya (Uti Possidetis: Journal of International Law, 2026)
Background: The COVID-19 pandemic exposed structural weaknesses in global health governance, particularly in unequal access to vaccines, health technologies, and financing between developed and developing countries. It also revealed the limitations of IHR 2005 in addressing such disparities. In response, the Pandemic Treaty was developed to strengthen the legal framework for global health emergencies. Methodology: This study employs a normative juridical approach based on literature analysis of key international legal instruments, guided by Lawrence O. Gostin’s framework of global solidarity for health equity. Objective: It examines the Treaty’s normative design in addressing justice-related gaps and analyzes the legal debates that shape the Treaty. The Findings: The research shows that the Treaty attempts to fill normative gaps in the IHR by introducing provisions on local manufacturing, technology transfer, pathogen access and benefit-sharing, transparency in procurement contracts, needs-based allocation, and collective financing mechanisms. However, the formulation of these provisions reflects ongoing legal debates regarding the choice of legal basis within the WHO framework, the degree of binding obligations, and the tension between mandatory and voluntary commitments. Originality: This study argues that the Treaty represents a normative shift toward equity-based global health governance, yet its effectiveness remains constrained by its reliance on soft-law formulations and political consensus. It highlights that these limitations are not merely technical but stem from deeper structural tensions within international law concerning sovereignty, equity, and global solidarity.